ROMANSY 21 -- Robot design, dynamics and control : proceedings of the 21st CISM-IFToMM Symposium, June 20-23, Udine, Italy /: proceedings of the 21st CISM-IFToMM Symposium, June 20-23, Udine, Italy. (2016) - Unknown
No abstract available